Il voto italiano all'estero Riflessioni, esperienze e risultati di un'indagine in Australia - Mascitelli, Bruno (Studi e saggi, 2012)
The novelties brought in by the legislature on the Italian vote abroad marked a turning point both for Italian politics, with the introduction of foreign representation, and for the communities of Italians abroad. But what opinion do our expatriate co-nationals have of the Italian vote? And has voting from abroad brought our global co-nationals closer (or not) to Italian politics, Italy and/or their Italian heritage? And then, who are the Italians in the world? How many are there and where are they concentrated? This book offers an up-to-date reading of the experiences of the Italian vote in the world from 2003 to date, analysis of the results of a survey into the participation of Italians abroad in the 2006 political elections, as well as cues, reflections and considerations on the topic of Italian emigration and the Italian vote abroad.